Presenilin, Notch, and the genesis and treatment of Alzheimer's disease - Selkoe, Dennis J. (The National Academy of Sciences, 2001)
Elucidation of the proteolytic processing of the amyloid β-protein precursor (APP) has revealed that one of the two proteases (γ-secretase) that cleave APP to release amyloid β-protein (Aβ) is likely to be presenilin. Presenilin also mediates the γ-secretase-like cleavage of Notch receptors to enable signaling by their cytoplasmic domains. Therefore, APP and Notch may be the first identified substrates of a unique intramembranous aspartyl protease that has presenilin as its active-site component. In view of the evidence for a central role of cerebral build-up of Aβ in the pathogenesis of Alzheimer's disease, this disorder appears to have arisen in the human population as a late-life consequence of the conservation of a critical developmental pathway.